Identyfikacja cech reżimu odpływu rzek w Polsce na różnych poziomach grupowania - Wrzesiński, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The paper presents the characteristics of the river regime types in Poland which were obtained by applying the unsupervised approach to the regime based on the results of clustering rivers with respect to the values of the 12 monthly flow coefficients in the average annual cycle. In the paper were used daily flow values from the period 1971–2010 for 516 gauges located on 280 Polish rivers.On three clustering levels, 5, 9 and 12 varieties of river runoff regimes were identified and detailed. The paper also presents the spatial distribution of rivers that represent these variants.
Keywords: river runoff; hydrological regime; hierarchical clustering; typology; flow coefficient (Pardé); unsupervised approach